2020
DOI: 10.1002/hpja.370
|View full text |Cite
|
Sign up to set email alerts
|

A critical food system program in South Australia and the effects on consumer knowledge and attitudes

Abstract: The food system is a complex network of inter-relationships between multiple elements and processes spanning the production, processing, packaging, distribution, consumption and waste of food. 1,2 It is well recognised that the food system intersects with compelling problems of modernity including malnutrition, chronic diseases, food insecurity, climate change, loss of biodiversity and unfair trade practices. 1 Hence, there is an imperative for sustainable diets, 1 defined by the Food and Agriculture Organisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The group interaction was a determining factor for the effectiveness of enutrir, reinforcing group value in nutrition education interventions (MEHTA et al, 2021;MURIMI et al, 2019;PETTIGREW et al, 2016). Literature shows that personal interactions and bonding are potential stimulants when learning about food and nutrition (BAUER; REISCH, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The group interaction was a determining factor for the effectiveness of enutrir, reinforcing group value in nutrition education interventions (MEHTA et al, 2021;MURIMI et al, 2019;PETTIGREW et al, 2016). Literature shows that personal interactions and bonding are potential stimulants when learning about food and nutrition (BAUER; REISCH, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Educational approaches that facilitate the understanding of the impacts that diet can have on the environment can increase the perception of participants on ecological issues that would exceed their individual experiences (GAYLIE, 2009;SUMNER, 2013). In consequence, ecological perception can foster sustainable and ethical food choices, expressed as behaviors such as reduced meat intake and local market purchases (MEHTA et al, 2021). To illustrate this comprehensive effect of the ecological dimension on others dimensions of food literacy in the context of our program, consider the following example.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is an urgent need to reduce meat consumption by replacing meat with plant-based foods (Jalil et al , 2020). In addition to being eco-friendly, a sustainable diet is healthy and socially equitable (Mehta et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the past ten years, several investigations have been conducted on sustainable consumption in higher education. Those investigations focused on different areas of consumption such as food and nutrition (Jalil et al , 2020; Johannisson and Hiete, 2021; Mehta et al , 2021; Scott et al , 2022; Soares Pinto et al , 2018; Yazdankhah et al , 2020), plastic waste (Berger, 2021; Bywater, 2014; Thongplew and Kotlakome, 2019; Tifferet et al , 2017), fashion and clothing (Baytar and Ashdown, 2013b; Joyner Armstrong et al , 2016; Rhee and Johnson, 2019; Sonnenberg et al , 2014) and energy (Lindelwa and Thondhlana, 2018; Parece et al , 2013). These investigations pursued two main objectives: to achieve a direct change in consumption behavior and to change perceptions, knowledge and attitudes regarding sustainable consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies showed that informational messaging reduced food waste by 15% (Whitehair, 2013;Pinto et al, 2018), while another study showed simply providing information didn't significantly impact the support for initiatives to reduce meat (De Groeve and Bleys, 2017). Shorter class-based interventions in the literature include a 50 min lecture showing a 4% increase in probability of purchasing a plant-based meal (Jalil et al, 2020), a two-week online intervention showing increased food knowledge (Mehta et al, 2020), a three-week course on water footprints that didn't significantly change consumption patterns (Godfrey and Feng, 2017), and a series of four class activities that increased student interest (Txurruka et al, 2016).…”
Section: Climate Changementioning
confidence: 99%